2022
DOI: 10.3390/vaccines10091435
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Trust and Consumption of COVID-19 Information Implicate a Mechanism for COVID-19 Vaccine and Booster Uptake

Abstract: Vaccine hesitancy remains a significant barrier to achieving herd immunity and preventing the further spread of COVID-19. Understanding contributors to vaccine hesitancy and how they change over time may improve COVID-19 mitigation strategies and public health policies. To date, no mechanism explains how trust in and consumption of different sources of information affect vaccine uptake. A total of 1594 adults enrolled in our COVID-19 testing program completed standardized surveys on demographics, vaccination s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Shyam Raman et al [ 39 ], Kavita Batra et al [ 19 ], Tesfaye Yadete et al [ 17 ], and Neil G Bennett et al [ 20 ] showed that Republicans expressed greater VBH than Democrats. Ruben Juarez et al [ 52 ]’s study underlines lack of faith in official information and sources significantly aggravated VBH. However, Marine Paridans et al [ 40 ] stated that hesitant groups in their study were not aligned with the vaccination plan.…”
Section: Resultsmentioning
confidence: 99%
“…Shyam Raman et al [ 39 ], Kavita Batra et al [ 19 ], Tesfaye Yadete et al [ 17 ], and Neil G Bennett et al [ 20 ] showed that Republicans expressed greater VBH than Democrats. Ruben Juarez et al [ 52 ]’s study underlines lack of faith in official information and sources significantly aggravated VBH. However, Marine Paridans et al [ 40 ] stated that hesitant groups in their study were not aligned with the vaccination plan.…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted in the United States (US) identified that individual-level degree of trust in (and consumption of) sources of COVID-19 information changed over time and were associated with COVID-19 initial series and booster uptakes. 10 Another US study found that political conservatism, male gender, lower level of education and low income were associated with low uptake of COVID-19 vaccines. 11 A study among caregivers of patients showed that increased care burden may lead to lower COVID-19 vaccine acceptance.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32][33][34][35][36] A recent study found that participants (n = 1594) who increased their trust in and consumption of official information sources, like healthcare providers and public health officials, were more likely to get a COVID-19 booster. 37 Our qualitative findings underscore how essential including recommendations to get a COVID-19 booster from trusted sources in health messaging and educational campaigns may be for increasing booster uptake.…”
Section: Discussionmentioning
confidence: 77%